2008
DOI: 10.1158/1055-9965.epi-08-0585
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Receptor Gene Variants Influence Susceptibility to Heavy Smoking

Abstract: Heavy smoking is a strong predictor of nicotine dependence, which is a major impediment to smoking cessation. Although both heavy smoking and nicotine dependence are highly heritable, previous attempts to identify genes influencing these phenotypes have been largely unsuccessful until very recently. We studied 1,452 heavy smokers (defined as smoking at least 30 cigarettes per day for at least 5 years) and 1,395 light smokers (defined as smoking <5 cigarettes per day for at least 1 year) to investigate the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
163
0
4

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 179 publications
(183 citation statements)
references
References 27 publications
15
163
0
4
Order By: Relevance
“…82 These predispositions were strongest if smoking began during adolescence. These finding are in correlation to those reported by Stevens et al, 90 who found two groups of SNPs in this cluster; one increased risk for heavy smoking, while the other was protective. 90 CHRNA5-CHRNA3-CHRNB4 and other substance abuse.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…82 These predispositions were strongest if smoking began during adolescence. These finding are in correlation to those reported by Stevens et al, 90 who found two groups of SNPs in this cluster; one increased risk for heavy smoking, while the other was protective. 90 CHRNA5-CHRNA3-CHRNB4 and other substance abuse.…”
supporting
confidence: 92%
“…These finding are in correlation to those reported by Stevens et al, 90 who found two groups of SNPs in this cluster; one increased risk for heavy smoking, while the other was protective. 90 CHRNA5-CHRNA3-CHRNB4 and other substance abuse. Comorbidity of nicotine and alcohol use is well documented but a common biological mechanism or genetic background has not been shown.…”
supporting
confidence: 92%
See 3 more Smart Citations